2015
DOI: 10.1002/anie.201502440
|View full text |Cite
|
Sign up to set email alerts
|

A Twist‐Bend Nematic (NTB) Phase of Chiral Materials

Abstract: New chiral dimers consisting of a rod-like and cholesterol mesogenic units are reported to form a chiral twist-bend nematic phase (NTB *) with heliconical structure. The compressibility of the NTB phase made of bent dimers was found to be as large as in smectic phases, which is consistent with the nanoperiodic structure of the NTB phase. The atomic force microscopy observations in chiral bent dimers revealed a periodicity of about 50 nm, which is significantly larger than the one reported previously for non-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
82
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(89 citation statements)
references
References 18 publications
5
82
2
Order By: Relevance
“…In fact, while the odd CBnCB molecules constitute the archetypical example of materials exhibiting the N TB phase [22,26,27,29], , -bis(4,40-cyanobiphenyloxy)alkanes (CBOnOCB) compounds do not appear to satisfy the necessary conditions, such as the curvature, to avoid crystallization and to show the N TB phase [37]. However, the intense work in the field during the last few years revealed the occurrence of N TB phases for a variety of etherlinked [24,39], hydrogen-bonded driven [40], imine-linked [28] odd dimers or nonsymmetric odd bimesogens containing chiral units [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, while the odd CBnCB molecules constitute the archetypical example of materials exhibiting the N TB phase [22,26,27,29], , -bis(4,40-cyanobiphenyloxy)alkanes (CBOnOCB) compounds do not appear to satisfy the necessary conditions, such as the curvature, to avoid crystallization and to show the N TB phase [37]. However, the intense work in the field during the last few years revealed the occurrence of N TB phases for a variety of etherlinked [24,39], hydrogen-bonded driven [40], imine-linked [28] odd dimers or nonsymmetric odd bimesogens containing chiral units [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…In 31 this phase, formed by achiral molecules, the director exhibits 32 periodic twist and bend deformations forming a conical helix 33 having doubly degenerate domains of opposite handedness. 34 Although initially described for dimers of the CBnCB family, 35 the discovery of a low temperature nematic phase boosted 36 research in the area, and a number of materials combining 37 different mesogenic units linked by chains have been identified 38 which exhibit the N TB phase [16][17][18] and its chiral counterpart 39 [19,20]. It is now recognized that molecular curvature plays 40 a crucial role in stabilizing the twist-bend nematic phase.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that many functional groups -including the SF 5 groupcan be incorporated into the structure of a suitable dimer without loss of the N TB phase. Last, the twistbend nematic phase -in dimers and bimesogens at least -is found mostly for methylene-linked materials, although a number of other linking groups are known to yield materials that afford this mesophase [7,21,22,33,[44][45][46][47][48][49]. In the first part of this paper, we present the latest part of our study into the structureproperty relationships of bis ether-linked dimers and bimesogens that exhibit the twist-bend phase.…”
Section: Introductionmentioning
confidence: 99%